2006
DOI: 10.1007/s00497-006-0023-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of the SSLP-based method for detection of rare apomictic events in a sexual AtSERK1 transgenic Arabidopsis population

Abstract: Here we present a screening method to evaluate the potential of genes to transfer aspects of apomixis into sexual crop plants. Based on the assumption that an apomictic progeny is an exact genetic replica of the mother plant we employed a set of single sequence length polymorphism (SSLP) markers to identify individuals displaying heterozygosity fixation in segregating sexual populations as an indication of rare apomictic events. Here we present the results of such a study using the Arabidopsis thaliana SOMATIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The somatic embryogenesis receptor kinase (SERK) may be an important component of somatic embryo initiation (Koltunow and Grossniklaus 2003). Kantama et al (2006) found rare maternal genotypes of putative adventitious embryony in AtSERK1 transgenic populations of Arabidopsis thaliana ; however, these genotypes were not heritable. Adventitious embryony does not show such a strong correlation to polyploidy (Richards 1997).…”
Section: Introductionmentioning
confidence: 89%
“…The somatic embryogenesis receptor kinase (SERK) may be an important component of somatic embryo initiation (Koltunow and Grossniklaus 2003). Kantama et al (2006) found rare maternal genotypes of putative adventitious embryony in AtSERK1 transgenic populations of Arabidopsis thaliana ; however, these genotypes were not heritable. Adventitious embryony does not show such a strong correlation to polyploidy (Richards 1997).…”
Section: Introductionmentioning
confidence: 89%
“…In Paspalum notatum, genetic fingerprinting with RAPD and RFLP molecular markers were used for determining the degree of apomictic reproduction of different tetraploid accessions and the effect of the pollination time on the proportion of sexual and apomictic offspring (Ortiz et al 1997;Espinoza et al 2002). Recently, a simple method for screening rare maternal progenies in diploid transgenic Arabidopsis based on heterozygous SSLP-markers was reported by Kantama et al (2006). On the other hand, flow cytometric seed screen (FCSS) methods are powerful tools for distinguishing between different modes of reproduction of plants involving sexual and apomictic development (Matzk et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Although natural apomixis does not occur in Arabidopsis, it is apparent that learning about the molecular mechanisms involved in apomixis from our best-characterized plant model systems is of great use. Tucker et al (2003) described two important techniques to study apomixis: the use of reproductive molecular markers derived from Arabidopsis in an apomictic plant system with established transformation procedures (such as Hieracium) and the use of comparative functional genetics to search and investigate the function of homologues of Arabidopsis reproductive genes in other plant systems (Eckardt 2003;Kantama et al 2006). Genes of the FIS-class are regulated by genomic imprinting and expressed only maternally at the early stages of seed development.…”
Section: Discussionmentioning
confidence: 99%